THE BIOLOGICAL ACTIVITIES OF HYPERICUM PERFORATUM L. - Okmen, Gulten; BalpÄ±nar, Neslihan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Mastitis reduces milk yield and alters milk composition. Antibiotics are widely used in the treatment of the disease. However, this widespread use of antibiotics causes both antibiotic residues in milks and antibiotic resistance developed in bacteria. Today’s researches are focused on discovering and using new antibiotics against bacteria.Objective: The aim of this work was to investigate the antibacterial effects of Hypericum perforatum L. extracts against mastitis pathogens, and its other biological activities. Material and Methods: The extracts were tested by disc diffusion assay. The MIC was evaluated on plant extracts as antibacterial activity. The non-enzymatic antioxidant activity was determined using DPPH as a free radical. Results: The extract showed maximum inhibition zone against two bacteria (Coagulase-negative staphylococci- 33 and 37; CNS 33 and 37), and the zone was 17 mm. A bacterium (CNS – 22) showed the lowest sensitivity to 812,5 µg /mL concentration. In addition, the extract was tested against the stable DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) free-radical for antioxidant activity. As a result, the extract displayed a strong antioxidant activity (trolox equivalent: 0,83 mM). Conclusion: The extract of Hypericum perforatum have antibacterial, antioxidant and antimutagenic potentials.